Log ODDS (LODDS) of positive lymph nodes as a predictor of overall survival in squamous cell carcinoma of the penis. Issue 8 (8th March 2021) - Patel, Keval N.; Salunke, Abhijeet; Bhatt, Supreet; Sharma, Mohit; Jain, Abhishek; Puj, Ketul; Rathod, Priyank; Warikoo, Vikas; Pandya, Shashank J.
Abstract: Objective: To evaluate the role of logarithmic ODDS (LODDS) in the number of positive lymph nodes and the number of negative lymph nodes as a prognostic metric in the squamous cell carcinoma (SCC) penis. Methods: Data were retrospectively collected from 96 cases of SCC penis that underwent bilateral groin dissection between 2010 and 2015 at our institute. Lymph node density (LND) and LODDS were calculated for all the patients and classified according to American Joint Committee on Cancer (AJCC) pN staging. Thresholds for LND (24% and 46%) and LODDS (−0.75 and 0) were established. Multivariate analysis of various cofactors was done with overall survival (OS) as a dependent factor. Three classification systems were compared using receiver operative characteristic (ROC) curve analysis. Results: Univariate analysis showed that AJCC pN, LND, and LODDS were all significantly correlated with OS. However, only LODDS (HR, 11.185; p  = .023) remained an independent prognostic factor through multivariate analysis. LODDS (log‐likelihood = 3832 vs. 3798; p  < .001) had better prognostic performance than pN and better discriminatory ability than LND (AIC = 3902 vs. 3928). LODDS had better power of discrimination than LND and pN. LODDS could predict survival in lymph node yield (LNY) < 15 ( p  < .001). Conclusion: LODDS is an independent predictor of OS in the SCC penis and has superior prognostic significance than the AJCC pN and LND classification systems.